(untitled) (Research, Society and Development, 2020)
The national market for cultivated fish is currently disputed by two species, tilapia (Oreochromis niloticus), which leads the Brazilian production, and panga (Pangasius hypophthalmus), a global highlight. Comparisons between the two species range from economic and management factors to sensory characteristics. Given this, the present study aimed to evaluate the quality of frozen fillets of O. niloticus and P. hypophthalmus through physical-chemical, microbiological and sensory analyzes. The frozen fillets of the two species were degassed and underwent chemical analysis: pH and total volatile bases (BVT); microbiological: search for Salmonella sp. and most likely number of coliforms at 35 and 45 ºC; physical: color (L * a * b *), water retention capacity (CRA), cooking weight loss (PPC) and shear strength (FC) and sensory assessing appearance, flavor, aroma, color, texture attributes and juiciness of the fillets. Higher pH and BVT values ​​were found in the panga samples. Microbiological analyzes showed that the fillets of both species were in compliance with current Brazilian legislation. Better results for CRA, PPC, FC and Color were found in the tilapia samples, indicating better quality of attributes such as juiciness and texture. The sensorial analysis revealed that tilapia was the most appreciated species among the tasters with superior evaluations appointed in the flavor, juiciness, texture and global impression attributes. Thus, this study allows us to conclude that there was a synergy between the results of physical analysis and sensory analysis, confirming the better quality of frozen tilapia fillet samples considering the evaluated parameters.